CloudEdge: a content delivery system for storage service in cloud environment. (1st October 2010) - Chiu, Chi-Huang; Lin, Hsien-Tang; Yuan, Shyan-Ming
With the trend of cloud computing, more and more web applications move their content to external storage services to reduce the cost of hardware and maintenance. In this paper, a novel architecture called CloudEdge for Content Delivery Network (CDN) with the storage service in cloud computing is introduced. This architecture could not only keep the loosely coupled integration between storage service and web applications but also provide better content manipulation features such as edge network content delivery, caching, secured access control, the variations of content objects generated on demand, and post-process on content objects.